Предмет: Математика,
автор: Аноним
Как решить задачу (6м3дм-4м7см)+(56дм-4м8см)-37дм5см=?
Ответы
Автор ответа:
2
Ответ:
0.
Пошаговое объяснение:
(6м3дм-4м7см)+(56дм-4м8см)-37дм5см =0
1. 6м3дм-4м7см = 6м30см - 4м7см = 2м23см.
2. 56дм-4м8см = 5м60см-4м8см = 1м52см.
3. 2м23см + 1м52см = 3м75см.
3. 3м75см - 37дм5см = 375см - 375см = 0.
Похожие вопросы
Предмет: География,
автор: huseinorujof
Предмет: Математика,
автор: Halbock
Предмет: Математика,
автор: alibostanov110511
Предмет: Математика,
автор: lilolol4
Предмет: Химия,
автор: Stafard